„Niewidzialny” ból – wykluczenie społeczne pacjentek z endometriozą. Analiza jakościowa - Kozik, Ewa (Kultura-Społeczeństwo-Edukacja, 2025)
The aim of this article is to analyze the social conditions that shape women’s experiences of endometriosis, with particular emphasis on the social perception of pain and societal responses to the disease. The article introduces the concept of “invisible” pain to describe the experiences of women who feel misunderstood, unaccepted, or even socially excluded due to their symptoms. It also presents strategies for coping with the illness, as well as the consequences of a lack of understanding from others – especially close relatives and medical professionals – on the well-being of those affected. The netnographic research involved women participating in Facebook-based online communities focused on endometriosis and other gynecological conditions. The collected data was analyzed using interpretative phenomenological analysis (IPA), which enabled a deeper understanding of the lived experiences of women with endometriosis. The findings aim to illustrate how women navigate the partial understanding of their illness, how they construct their illness narratives, and the role that online support groups play in this process. This research may serve as a starting point for further exploration of the relationship between people living with chronic illness and the society around them.